The Burns Registry of Australia and New Zealand: progressing the evidence base for burn care. Issue 5 (21st March 2016) - Cleland, Heather; Greenwood, John E; Wood, Fiona M; Read, David J; Wong She, Richard; Maitz, Peter; Castley, Andrew; Vandervord, John G; Simcock, Jeremy; Adams, Christopher D; Gabbe, Belinda J
Abstract: Objective: Analysis of data from the Burns Registry of Australia and New Zealand (BRANZ) to determine the extent of variation between participating units in treatment and in specific outcomes during the first 4 years of its operation. Design: BRANZ, an initiative of the Australian and New Zealand Burn Association, is a clinical quality registry developed in accordance with the Australian Commission on Safety and Quality in Healthcare national operating principles. Setting: Patients with burn injury who fulfil pre‐defined criteria are transferred to and managed in designated burn units. There are 17 adult and paediatric units in Australia and New Zealand that manage almost all patients with significant burn injury. Twelve of these units treat adult patients. Participants: Data on 7184 adult cases were contributed by ten acute adult burn units to the registry between July 2010 and June 2014. Major outcomes: In‐hospital mortality, hospital length of stay, skin grafting rates, and rates of admission to intensive care units. Results: Considerable variations in unit profiles (including numbers of patients treated), in treatment and in outcomes were identified. Conclusions: Despite the highly centralised delivery of care to patients with severe or complex burn injury, and the relatively small number of specialist burn units, we found significant variation between units in clinical management and in outcomes. BRANZ data from its first 4 years of operation support its feasibility and the value of further development of the registry. Based on these results, the focus of ongoing research is to improve understanding of the reasons for variations in practice and of their effect on outcomes for patients, and to develop evidence‐informed clinical guidelines for burn management in Australia and New Zealand.